MicroRNA‐124 Protects Neurons Against Apoptosis in Cerebral Ischemic Stroke - Sun, Yang (CNS Neurosci Ther, 2013)
AIMS: To explore the role and underlying mechanism of miR‐124 in stroke. METHODS: miR‐124 expression was determined by real‐time PCR. The effect of miR‐124 on infarct area was assessed in middle cerebral artery occlusion (MCAO) mice. The influence of miR‐124 on oxygen and glucose deprivation (OGD) induced neuron apoptosis and death was examined by immunofluorescence. The effect of miR‐124 on apoptosis‐related proteins was determined by Western blot. RESULTS: The level of miR‐124 is significantly increased in ischemic penumbra as compared with that in nonischemic area of MACO mice. Brain tissue of stroke‐prone spontaneously hypertensive rats (SHR‐SP) also showed higher level of miR‐124 as compared with that of spontaneously hypertensive rats (SHR). Consistently, OGD treatment obviously increased miR‐124 level in primary neurons. In vivo, miR‐124 overexpression significantly decreased, while miR‐124 knockdown significantly increased, the infarct area of MCAO mice. In vitro, gain or loss of miR‐124 function resulted in reduced or increased neuron apoptosis and death induced by OGD, and increased or reduced antiapoptosis protein, Bcl‐2 and Bcl‐xl, respectively. CONCLUSIONS: miR‐124 plays a neurons‐protective role via apoptosis‐inhibiting pathway in ischemic stroke.